Inflammatory mediators causing cutaneous chronic itch in some diseases via transient receptor potential channel subfamily V member 1 and subfamily A member 1 - Xie, Bo; Li, Xin‐Yu (Journal of dermatology, 2019)
Chronic itch with an itch–scratch vicious circle is a significant problem in a large amount of diseases. Some of these diseases, such as psoriasis, atopic dermatitis, prurigo nodularis, Sézary syndrome, uremic pruritus, diabetes and jaundice, are common. For a very long time, chronic itch has been a thorny problem with few effective treatments. Because of this, itch researchers and dermatologists seek to find the mechanisms among chronic itch, inflammatory cytokines and neurons. As an immediate area of research focus, we are going to find the peripheral cross‐talk between neurons and skin cells. Two receptors, named transient receptor potential channel vanilloid 1 and transient receptor potential channel ankyrin transmembrane protein 1, have been shown to play important roles in chronic itch. Many advances have been made so far this decade. This review talks about the updated mechanism of itch‐related inflammatory cytokines via transient receptor potential channels in cutaneous chronic itch and corresponding diseases. The search for itch‐related inflammatory mediators and the structure of transient receptor potential channels this decade could deepen our understanding of the mechanism of itch and help us find more treatments of chronic itch in the future.